2021
DOI: 10.1007/s42452-021-04172-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the foam-forming of non-woven lightweight fibrous materials using X-ray tomography

Abstract: Foam-forming has in the past predominantly been used to create two-dimensional sheet-like fibrous materials. Allowing the foam to drain freely and decay under gravity, rather than applying a vacuum to remove it rapidly, we can produce lightweight three-dimensional fibrous structures from cellulose fibres, of potential use for thermal and acoustic insulation. $$\mu$$ μ CT scanning of the fibrous materials enable us to determine both void size distributions and also distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Liquid foams are excellent model systems for complex cellular structures, and foams including elastic membranes as the one we describe here could have potential relevance for tissue growth [28]. Interactions between foams and flexible slender structures also occur in widely used fabrication techniques such as foam-forming of cellulose for the paper industry [29,30]. Finally, using a UV-curable system, we have proposed a way to mold materials with characteristic shapes and curves resulting from the elasto-capillary competition.…”
Section: Discussionmentioning
confidence: 97%
“…Liquid foams are excellent model systems for complex cellular structures, and foams including elastic membranes as the one we describe here could have potential relevance for tissue growth [28]. Interactions between foams and flexible slender structures also occur in widely used fabrication techniques such as foam-forming of cellulose for the paper industry [29,30]. Finally, using a UV-curable system, we have proposed a way to mold materials with characteristic shapes and curves resulting from the elasto-capillary competition.…”
Section: Discussionmentioning
confidence: 97%
“…Foam-formed fiber networks have a unique microporous structure with planar structural variation originating from bubbles, [77,130] as discussed earlier in Sections 5.2 and 5.3. Moreover, X-ray microtomography has shown that fiber networks tend to form separate layers in the thickness direction at very low average material density.…”
Section: Fiber Network Structurementioning
confidence: 95%
“…Despite this rather drastic change in the fiber foam structure, traces of bubble structure still remain visible in the final dried sheet. [21,77,129,130] Al-Qararah [22] showed that lower density can be achieved in a sheet sample by using foam as the carrier phase instead of water with equal surfactant concentration. Thus, the bubble structure is essential in setting the densitynot only the reduced bonding because of surfactant.…”
Section: Materials Densitymentioning
confidence: 99%
See 2 more Smart Citations